Regulation of plant responses to temperature stress: a key factor in food security and for mitigating effects of climate change - Lee, Ziwei; Lim, Jie Ann; Harikrishna, Jennifer Ann; Islam, Tofazzal; Abd Rahim, Muhamad Hafiz; Yaacob, Jamilah Syafawati (Springer Science and Business Media Deutschland, 2024)
Among the many threats to food security, extremes of temperature, and unpredictable changes in temperature such as unseasonal frost or snowfall resulting from climate change have significant impacts on crop productivity and yields. It has been projected that for each increase by 1 °C of the global temperature, agricultural outputs of some staple food crops will decline by up to 3–8%. Alarmingly, reports from the National Aeronautics and Space Administration (NASA) and National Oceanic and Atmospheric Administration (NOAA) have revealed that our earth experienced one of the warmest summers in 2022, indicating that temperature stress is not a threat that can be taken lightly. Global food prices have risen by more than 70% since the middle of 2020, however, the UN Food and Agriculture Organization (FAO) projects that by 2027, the combined effects of climate change, conflict and poverty may lead to an additional rise in food prices by 8.5%. Taken together, the impacts of extreme temperatures on staple food supply amplify the risks of child malnutrition and food insecurity, especially in less-developed countries. This review offers a novel perspective on the intricate interplay between plant responses to heat and cold stresses, aiming to pave the way for innovative and efficient crop improvement programs crucial for ensuring a resilient and sustainable food supply in the face of climate change. A thorough and comprehensive understanding on plant mechanisms can effectively help agricultural industry to produce stress-resilient and climate-tolerant crops. Also, with the assistance from robust breeding techniques and genetic tools, the goal to achieve sustainable food supply chain can be attained.